Turkey : Selected Issues. (IMF Staff Country Reports; Country Report, 2019)
This Selected Issues paper on Turkey assesses the role of structural reforms in enhancing productivity growth in advanced and emerging economies and discusses results that are relevant for Turkey. The paper investigates the role of structural reforms in boosting productivity growth and describes the stochastic frontier set-up for analyzing factors that affect output through technical efficiency; and subsequently presents empirical results. It also simulates productivity gains from closing the structural reform gaps between Turkey and its benchmark. Structural reforms to improve hiring and firing regulations, the business and regulatory environment, and skills are found to have the largest estimated long-term productivity gains for Turkey. In order to bolster Turkey's sustainable medium-term growth prospects, structural reforms should be implemented sooner rather than later, and any possible negative reform impacts in the short run could be limited by a reform sequencing and reform complementarities.